(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Transportation plays important factor in broiler industry. Whole transportation process from loading to unloading can cause stress to broilers. The duration of the trip can affect oxidative stress, physiological and performance of broiler. This study aim to evaluate the effects of different transportation durations on oxidative stress, physiological responses and performance of broilers. Transportation from farm to slaughterhouse using a truck with a capacity of 144 crates. There were two durations treatment in this study, 180 and 240 mins. Variables measured in this study were oxidative stress indicators (malondialdehyde/ MDA content and catalase enzyme activity), physiological responses (rectal temperature and heterophile lymphocytes (HL) ratio), and performance represented by weight loss percentage. Normality test was done before T Test. Data analyzed using T Test independent which compared data between before and after transportation. T Test dependent which compared data between short and long duration. The result showed that duration of transportation significantly affects on decrease liver and thigh catalase enzyme activity, decrease malondialdehyde value on liver, decrease HL ratio after transportation, differences on rectal temperature and weightloss. Long transportation duration resulted the lowest liver and thigh catalase enzymes activity (0.097±0.023 and 0.088±0.014 U/mL). It can be concluded that the long duration transportation catalase enzyme activity reduce MDA value and affected performance indicator